Novelty vs. Familiarity Principles in Preference Decisions: Task-Context of Past Experience Matters - Liao, Hsin-I; Yeh, Su-Ling; Shimojo, Shinsuke (Frontiers in Psychology, 2011)
Our preferences are shaped by past experience in many ways, but a systematic understanding of the factors is yet to be achieved. For example, studies of the mere exposure effect show that experience with an item leads to increased liking (familiarity preference), but the exact opposite tendency is found in other studies utilizing dishabituation (novelty preference). Recently, it has been found that image category affects whether familiarity or novelty preference emerges from repeated stimulus exposure (Park, Shimojo, and Shimojo, PNAS 2010). Faces elicited familiarity preference, but natural scenes elicited novelty preference. In their task, preference judgments were made throughout all exposures, raising the question of whether the task-context during exposure was involved. We adapt their paradigm, testing if passive exposure or objective judgment task-contexts lead to different results. Results showed that after passive viewing, familiar faces were preferred, but no preference bias in either direction was found with natural scenes, or with geometric figures (control). After exposure during the objective judgment task, familiar faces were preferred, novel natural scenes were preferred, and no preference bias was found with geometric figures. The overall results replicate the segregation of preference biases across object categories and suggest that the preference for familiar faces and novel natural scenes are modulated by task-context memory at different processing levels or selection involvement. Possible underlying mechanisms of the two types of preferences are discussed.